Implementation Realities of NEP 2020: Infrastructural Gaps, Teacher Shortages, and the Digital Divide in Rural India - Kamble, Charandas Yuvraj (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The National Education Policy (NEP) 2020, unveiled five years ago, represents India’s most ambitious educational reform in decades, envisioning a holistic, flexible, and technology-driven education system rooted in Indian values and global competitiveness. However, the gap between policy vision and implementation reality has become increasingly evident, particularly in rural India. This paper critically examines the implementation challenges of NEP 2020 through three interrelated dimensions: infrastructural gaps, teacher shortages, and the digital divide in rural contexts. Drawing on secondary data from government sources including UDISE+ 2023–24, ASER 2024, and the QS I-GAUGE implementation progress report, alongside qualitative insights from educationists and policy analysts, the study employs a mixed-methods systematic review approach. Key findings reveal stark inequities: only 57.2% of schools have functional computers, 53.9% have internet access, and merely 35% host smart classrooms. Teacher shortages exceed 8.46 lakh positions nationally, with rural areas disproportionately affected, while over 70 lakh teachers have undergone digital training through platforms like DIKSHA and NISHTHA, yet pedagogical integration remains limited. The paper argues that without addressing these foundational gaps, NEP 2020 risks reinforcing rather than remedying the "India-Bharat divide." The study proposes a multi-stakeholder framework for equitable implementation, emphasizing targeted infrastructure investment, teacher education reform, and community-engaged digital inclusion strategies.